Dancing pirate (Digiview Productions, 2004)
Rita Hayworth makes a brief, but memorable, appearance in this musical tale of dancing pirates and step-lightly buccaneers. Featuring a score by legendary composers Rogers and Hart, the Dancing Pirate follows the comical adventures of Jonathan Pride (played by British stage veteran Charles Collins), a dance instructor who falls in with a gang of zany pirates, and ends up being mistaken for their chieftain. Frank Morgan (of MASH TV series fame) costars.